Role Of Adventure Tourism In The Local Market: Current Segment And Developments - Tilovmurodov Dostonbek (Peerian Journals Publishing, 2024)
This special issue of the tourism market explores several aspects of adventure tourism. Therefore, this article focuses on covering all related subjects such as recent development, demand and supply, contribution, eco, and sustainable tourism, combination with well-being and health, methodological challenges, relevance for developing countries, demographic change, desired experiences, spatial requirements for outdoor recreation, and adventure tourism in Uzbekistan. This special issue broadens the scope of the fascinating and important of adventure tourism.
Keywords: tourism; tourism market; adventure tourism; tourism role